Physical functioning and life style of 50-65 years’ age hee teachers - Baskevich, O.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to study life style of 50-65 years’ age university teachers depending on their physical functioning and its connection with behavior habits. Material: questioning of 150 respondents was fulfilled by specially prepared questionnaire. Anthropometric testing was conducted. Results: it was found that most of the questioned spend time watching TV or reading and pay very little attention to physical functioning. We also found that most of respondents deal with household chores but want to do something outdoors (practice public activity). There is a trend to avoid smoking among them. Only 5.0% are cigarette smokers. The rest have never smoked or gave up smoking more than 10 years ago. Among the partners of the questioned there are a lot of smokers (16.2%). Most of the questioned have friends and relatives, who can help to achieve the highest level of physical functioning. 18.9% of partners of the questioned regularly practice sports. Some useful for health habits are observed in life situations of all respondents. Conclusions: the received data witness about purposefulness of seeking of effective ways of pre retirement age HEE teachers’ involvement in active recreational functioning. We have also found that there are time reserves for this purpose.